From teratoma to sarcoma: unveiling a rare somatic transformation in a mediastinal germ cell tumor - Krishnakumar, Keerthika; Shivalingappa, Shivakumar Swamy; Ashok, Mahesh; Gowda, Thasmai B. R. (International Journal of Advances in Medicine, 2025)
Germ cell tumors (GCTs) are neoplasms primarily arising from gonadal tissues, occasionally occurring in extra gonadal sites. Though generally responsive to chemotherapy, a rare complication is the development of somatic malignancy within the tumor, such as sarcomas or carcinomas, leading to poorer prognosis and complex management. They are driven by genetic/epigenetic changes and dedifferentiation of pluripotent cells. Here we present a rare case of 31-year-old male with malignant peripheral nerve sheath tumor (MPNST) subtype of somatic-type malignancy within a mediastinal GCT.